Reading Interest in Class VI Students of Elementary School 2 Terban Reading Interest in Class VI Students of Elementary School 2 Terban - Hasna', Gahita Alifah; Kamila, Umniati; Salsabila, Firdhausa; Safitri, Nandhini Syifa' Aulia; Pangesti, Dewi Wahyu (Jurnal Inovasi Pembelajaran Karakter, 2024)
This study aimed to explore the reading interest of grade VI students at SD 2 Terban and the factors that influence it. A descriptive qualitative approach was used in the research. The participants were grade VI students at SD 2 Terban, and data was collected through observation, interviews, and documentation. The findings showed that students' reading interest was still relatively low, as indicated by their infrequent visits to the library. Most students preferred staying in class and talking with friends rather than reading books in the library. The low reading interest was attributed to a lack of interest, insufficient attention to books, limited understanding of the benefits of reading, and a lack of motivation from both internal and external factors. Internal factors influencing reading interest included emotions, attention, and motivation, while external factors involved the role of teachers, the environment, family, and available resources. To improve reading interest, it is crucial to provide consistent motivation and attention to grade VI students. Furthermore, teachers should apply appropriate teaching strategies to help students understand the material more effectively. The school library, as a valuable learning resource, should be properly managed, including the implementation of a computerized system to help students easily find books, which could ultimately enhance their reading interest.